2020
DOI: 10.1111/jfbc.13434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a dietary supplement composed of hydrolyzed milk proteins and vanillin on the reduction of infection and oxidative stress induced by chemotherapy

Abstract: Cytotoxic chemotherapy plays an important role in the treatment of cancer. Two major complications of chemotherapy are oxidative stress-induced side effects and infections. Oxidative damage to cells and tissues is caused by free radicals and active oxygen metabolites during cancer development and its treatment course (Abdel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Vanillin (4-hydroxy-3-methoxy benzaldehyde, Van) and ethyl vanillin (EVA) belong to aroma chemicals obtained from Kraft lignin [ 1 ], microorganism fermentation [ 2 ] or chemical synthesis [ 3 ], which are in-demand largely because they can be used as food additives [ 4 ], antimicrobial [ 5 ], anti-inflammation [ 6 ], and anti-cancer [ 7 ] drugs, or as optical material [ 8 ]. As early as 1991, Singh et al [ 9 ] found that Van/EVA crystals were polymorphic with conventional type I and type Ⅱ crystallized from chloroform-carbon tetrachloride solution but type Ⅲ and type Ⅳ only discovered from molten state.…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin (4-hydroxy-3-methoxy benzaldehyde, Van) and ethyl vanillin (EVA) belong to aroma chemicals obtained from Kraft lignin [ 1 ], microorganism fermentation [ 2 ] or chemical synthesis [ 3 ], which are in-demand largely because they can be used as food additives [ 4 ], antimicrobial [ 5 ], anti-inflammation [ 6 ], and anti-cancer [ 7 ] drugs, or as optical material [ 8 ]. As early as 1991, Singh et al [ 9 ] found that Van/EVA crystals were polymorphic with conventional type I and type Ⅱ crystallized from chloroform-carbon tetrachloride solution but type Ⅲ and type Ⅳ only discovered from molten state.…”
Section: Introductionmentioning
confidence: 99%
“…Some bioactive molecules, such as lactoferrin, EGF, and TGF-β, resist enzyme digestion, while others can be produced by enzymatic hydrolysis of whey protein in vivo and in vitro [ 11 , 24 , 25 ]. Bioactive peptides exert beneficial health effects by affecting metabolism (glucose, fat, and amino acids) [ 26 , 27 , 28 , 29 ]. Moreover, whey protein extract stimulated neutrophils and lymphocytes [ 30 , 31 , 32 ], and feed containing fermented whey protein lowered the levels of infiltrating neutrophils in atopic contact dermatitis in mice [ 33 ].…”
Section: Introductionmentioning
confidence: 99%